The Effect of Long Drying on the Chemical and Organoleptic Characteristics of Excelsa Coffee Skin Tea (Coffee liberica var. dewevrei) - Karima, Ummi; Hartati, Dyah Ayu Sri; Chusnah, Miftachul (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Handling coffee skin waste has caused problems because it is left to rot, stacked, and burned which can cause negative impacts on the surrounding environment so it needs to be overcome. One way that can be done is to utilize these natural resources by processing coffee skin waste into processed or other products with high economic value, namely coffee skin tea. This study aims to determine (1) the effect of drying time on the chemical characteristics of coffee skin tea products (cascara) and (2) the effect of drying time on the organoleptic of coffee skin tea which includes color, aroma, and taste. The method used in this study is an observation method with a qualitative data approach. This method used two subjects, namely chemical and organoleptic characteristics in tea, to be observed within one month. The results showed that different drying times can have a noticeable effect (P<0.05) on tannin and caffeine levels and changes in color, aroma, and taste in tea steeping. The ideal drying time treatment is 5 hours with a caffeine content of 0.26 grams, tannin content of 283.33 ppm, dark red steeping color, a very inactive aroma, and a delicious tea taste.